Peran PPK Sumbermanjing Wetan dalam Meningkatkan Partisipasi Masyarakat pada Pemilu dan Pilkada Tahun 2024 - Iyza Ayundha Putri; Rissa Ayustia (Lembaga Pengembangan Kinerja Dosen, 2025)
The community as voters has a very important role because it is one of the factors that determine the success or failure of organizing elections. The purpose of this research is used as information on the role of election organizers, in this case the District Election Committee (PPK) at the Sumbermanjing Wetan District Level, Malang Regency in its efforts to increase community participation and as knowledge about general elections to be used as an evaluation in organizing future elections. This research uses phenomenological qualitative research methods through in-depth source interviews and observation notes to election organizers, namely members of the District Election Committee (PPK) in Sumbermanjing Wetan District, Malang Regency. PPK in socialization activities to the community cooperates with the District Election Supervisory Committee (Panwascam) in supervision and socialization, government agencies, government institutions and local village community organizations in disseminating socialization to the community because it is able to reach all communities that have limited accessibility. The declining level of community participation needs to be reviewed so that people who abstain from voting or who do not use their voting rights can actively participate in realizing democracy. In addition, a wise evaluation of the regulations, technical implementation, accuracy of voter data, neutrality and integrity of the electoral process is needed.